A escrita na formação inicial docente: o que escrevem os futuros professores? - Baptistella, Bruna Fabiane [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work investigates writing practices promoted in a Pedagogy course of a Brazilian public university in the context of subjects offered in the curriculum, in the university extension projects (Dean of University Extension - PROEX), the Teaching Core Program projects (Dean of Undergraduate Studies - PROGRAD) in Pibid (Institutional Program of Introduction to Teaching - Capes) and in interviews with students of that course. The overall objective is to investigate the potential of the writing practice in initial teacher education and, specifically, to describe and to discuss the future teachers' writing practices in the course, explaining on how they understand them and how they see their contributions to the teacher training. The sight of students in relation to the writing practice was related to what was described in the Pedagogical Political Project (PPP) of that course and the summary of the subjects. Inspired by the research perspective of thematic oral history, data were produced through semi-structured interviews with seven female students and one male student, who, at the time of the survey, were enrolled from first to fourth year of Pedagogy. Those subjects were chosen according to some criteria: four who are doing the course and four that are doing the course and extension projects, projects of the Teaching Center Program or Pibid. From their statements and the documentary research we could find evidences to think that what is written in the context of initial training involves three areas: official written, marginal written and experiential written. This study makes it possible to discuss the initial teacher training in those formative spaces of the university, as well as reflect on the writing practices as a formative potential, both in the professional sphere as in the personal sphere

Este trabalho investigou as práticas de escrita promovidas em um curso de Pedagogia de uma universidade pública brasileira, no contexto das disciplinas oferecidas na grade curricular, nos projetos de extensão universitária (Pró-Reitoria de Extensão Universitária - PROEX), nos projetos do Programa do Núcleo de Ensino (Pró-Reitoria de Graduação - PROGRAD), no Pibid (Programa Institucional de Iniciação à Docência - Capes) e em entrevistas com alunos desse curso.O objetivo geral consistiu em investigar a potencialidade das práticas da escrita na formação inicial de professores e, de maneira específica, inventariar e problematizar as práticas da escrita dos futuros professores no curso, explicitando de que forma eles as compreendem e como enxergam suas contribuições para a formação docente. A visão dos estudantes em relação à prática de escritafoi relacionada ao que se anunciava no Projeto Político-Pedagógico (PPP) do referido cursoe nas ementas das disciplinas.Inspirada na perspectiva de pesquisa da História Oral Temática, os dados foram produzidos por meio de entrevistas semiestruturadas com sete alunas e um alunoque, no momento da pesquisa, cursavam do primeiro ao quarto ano de Pedagogia. Tais sujeitos foram escolhidos de acordo com alguns critérios: quatro que faziam o curso e outros quatro que além do curso participavam de projetos de extensão, de projetos do Programa do Núcleo de Ensino ou do Pibid. A partir de suas falas e da pesquisa documental foi possível encontrar indícios para se pensar que o que se escreve no contexto da formação inicial passa por três eixos: de escritas oficiais, de escritas marginais e de escritas experienciais. Este estudo possibilita discutir a formação inicial docente nos referidos espaços formativos da universidade, assim como refletir acerca das práticas de escrita como potencialidade formativa, tanto na esfera profissional como pessoal
Keywords: Teachers, Training of; Professores - Formação; Escrita; Pratica de ensino